Smart Communities. Social Innovation at the Service of the Smart Cities - Bencardino, Massimiliano; Greco, Ilaria (TeMA - Journal of Land Use, Mobility and Environment, 2014)
Making Cities Smarter is the challenge of the new millennium, even in a context of profound structural crisis like the present one. In fact, there is an urgent need to rethink the models of socio-economic development to make them more consistent with the new social needs, in particular related to the territorial liveability and social inclusion. In the literature produced in recent years and that has stimulated reflections, ideas, research and projects for a smart urban development, a “smart city” is generally meant as a city capable of joining “competitiveness” and “sustainability”, by integrating different dimensions of development (economic, mobility, environment, people, living and governance).  However, the actions have been largely focused on ICTs and their impacts on urban development.This contribution starts from a reflection, already begun by the authors, on the theme of “Smart City” as “Senseable city”, which means that we need to focus the discussion no more on “how cities can be smarter” but on “how intelligent technologies can lead us to rethink the patterns of urban development by making them fair and inclusive, as well as efficient and sustainable”. In this paper, the attention is focused on another aspect that in recent years is becoming increasingly important in terms of the development of smart cities, that is the social innovation, understood as innovative practice with the aim of creating a positive impact for society that is as wide as possible. The direct and indirect impact that the creation of social innovation can exercise in terms of urban development will lead us to talk about different models of Smart Cities as “Social Cities”. Finally, investigating the Italian experience, the article shows how, despite the efforts, the current approaches to the problem are still very far from considering a Smart City as a local system focused on innovation, a system in which the application of new technologies is not random but responds to a strategic project that starts from the bottom, from the real needs of the citizen.